Optimization and standardization of oil extraction from Malunggay (Moringa oleifera) seeds - Tan, Sheila Erica S.; Rumbaoa, Rowena Grace O. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
Crude Moringa Oleifera oil was extracted using batch solvent extraction with hexane as the solvent. The optimized extraction time was determined to be at 6 hours with a yield of 25.3672 ± 0.0898% oil. The extraction process was standardized with its yield and other chemical properties as parameters. Obtained malunggay oil showed no significant difference in oil yield during standardization. The oil presented a FFA range of 6.3-6.8% expressed as oleic acid, iodine value range of 59.7 to 59.9 and saponification value of 166 to 168. The color based on the red and yellow values observed using the 1- inch cell of a Lovibond tintometer, was 0.3r and 75y, respectively, indicating a strong yellow color with a tinge of red. Based on the results, malunggay oil does have the capability to be used as cooking oil, but first, refinement must be done to ensure that it is safe for consumption.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Moringa oleifera